2002
DOI: 10.1111/1467-8624.00450
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Teaching: The Development of Teaching Skills in Maya Sibling Interactions

Abstract: Psychology has considered the development of learning, but the development of teaching in childhood has not been considered. The data presented in this article demonstrate that children develop teaching skills over the course of middle childhood. Seventy-two Maya children (25 boys, 47 girls) ranging in age from 3 to 11 years (M = 6.8 years) were videotaped in sibling caretaking interactions with their 2-year-old brothers and sisters (18 boys, 18 girls). In the context of play, older siblings taught their young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 63 publications
(54 reference statements)
8
114
0
14
Order By: Relevance
“…Few researchers completely discourage praise, or claim that it is totally unnecessary (Kohn, 1993) while cultural psychologists claim that praise is not universally necessary or commonplace, since it does not exist in all cultures (Maynard, 2002). However, Meyer (1992) found that praise and other behaviors such as pity, help, assignment of easy tasks, which are mostly regarded as positive and desirable, can actually have negative impacts as they can unintentionally convey messages of perceived low-ability.…”
Section: The Negative Impact Of Praisementioning
confidence: 99%
“…Few researchers completely discourage praise, or claim that it is totally unnecessary (Kohn, 1993) while cultural psychologists claim that praise is not universally necessary or commonplace, since it does not exist in all cultures (Maynard, 2002). However, Meyer (1992) found that praise and other behaviors such as pity, help, assignment of easy tasks, which are mostly regarded as positive and desirable, can actually have negative impacts as they can unintentionally convey messages of perceived low-ability.…”
Section: The Negative Impact Of Praisementioning
confidence: 99%
“…a' ech to vi La actividad 2 muestra que la interacción entre pares juega un rol importante en la enseñanza e involucramiento de niños en las pequeñas actividades cotidianas (De León, 2005Goodwin, 1990;Goodwin y Kyratzis, 2011;Maynard, 2002;Rogoff, 1990. La secuencia de interacción entre los hermanitos muestra cómo la niña por iniciativa propia hace un collar a partir de eventos concretos que ha vivido y observado de los adultos que enrollan hilos o lazos sobre el pie o la pierna.…”
Section: El Habla-en-interacción Vista Desde La Multimodalidadunclassified
“…Estudios desde la teoría cultural de la actividad muestran que los niños en contextos indígenas (en Guatemala con mayas ts'utujiles, en México con mayas yucatecos, mayas tsotsiles de Zinacantán y mazahuas, entre otros), desde pequeños, tienen oportunidad de observar el trabajo adulto y de incorporarse como participantes en diversas actividades (Cancian, 1964;Chavajay 1993;Chavajay y Rogoff, 1999;Chamoux, 1992;Childs y Greenfield, 1980;de Haan, 1999;Gaskins, 1999Gaskins, , 2010Gaskins y Paradise, 2010;Greenfield y Childs, 2005;Maynard et al, 2003;Maynard, 2002;Modiano 1973;Rogoff et al, 2003;Morelli et al, 2003;Paradise ,1996;Paradise y Roggoff, 2009).…”
Section: Introductionunclassified
“…"Qualitative" included analyses of non-numerical data (Gall et al;Sandelowski, 2001). Since research often does not fit cleanly into this dichotomy (Creswell & Plano Clark, 2006), we defined "both" operationally as an article including numerical and non-numerical data, such as results including frequency data on categories that emerged from coding (e.g., Maynard, 2002;Suárez-Orozco, Gaytán, Bang, Pakes, O'Connor, & Rhodes, 2010).…”
Section: Materials and Proceduresmentioning
confidence: 99%